Aplicación de búsqueda y reserva de sitio de parqueo (parkingapp) (2021)
The aim is to develop a technological solution that performs the operations of search and reservation of a parking place in the city of Bogota. This pretension will be carried out through the construction of a mobile application and a web application for parking management and the administration of a platform. This paper will show the contextual analysis work and the engineering process carried out for the construction of the artifacts estimated for the proposed solution. Starting from this context and using the available means, it is possible to design and build a geo positional information system that, in real time, solves the problem.